1988
DOI: 10.1002/bem.2250090406
|View full text |Cite
|
Sign up to set email alerts
|

Microwave effects on acetylcholine‐induced channels in cultured chick myotubes

Abstract: The behavior of cultured myotubes from chick embryos exposed to microwaves has been experimentally analyzed. Recordings of acetylcholine-induced currents have been obtained via patch-clamp techniques using both cell-attached (single-channel current recording) and whole-cell (total current recording) configurations. During the exposure to low-power microwaves the frequency of the ACh-activated single channel openings decreased, while the ACh-induced total current showed a faster falling phase. Channel open time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, we reject this mechamsm primarily due to (i) the opposite effects of the field on the channels with high and low affinity for Ca 2+ and (ii) the absence of any effect of the field on the unit channel conductance y. There are also other reasons why this mechanism is unacceptable [3,10,18].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, we reject this mechamsm primarily due to (i) the opposite effects of the field on the channels with high and low affinity for Ca 2+ and (ii) the absence of any effect of the field on the unit channel conductance y. There are also other reasons why this mechanism is unacceptable [3,10,18].…”
Section: Resultsmentioning
confidence: 97%
“…A horizontal line indicates the expected behaviour of the relationship in the absence of the EMF effect on n. As can be seen, ifn ° is, on average, more than 1, the field reduces it; conversely, if n ° is less than 1, the field would increase it. Thus, the degree and direction of the EMF effects on the parameters of the Kca channels depend on their initial biological status (see also [1,6,18]). What is a possible mechanism of the observed effects of the microwaves on the Kca channels?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But opsonized zymosan is very complex stimulus to analyse the intracellular mechanisms. Nonthermal effects of continuous mm waves were revealed in studies of various membrane functions [D'Inzeo et al, 1988;Kataev et al, 1993;Geletyuk et al, 1995;Pakhomov et al, 1997]. In contrast, it was shown that a thermal mechanism underlies the effects of mm waves on ionic currents of Lymnaea neurons [Alekseev and Ziskin, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, several reports have supported the concept that the cell membranes of the brain are critical structures perceiving the action of microwaves (D'Inzeo et al, 1988;Adey, 1993), which is reflected in the underlying neurochemical profile (Merrit et al, 1976;Kunjilwar and Behari, 1993;Lai, 1994;Yurinskaya et al, 1996) and the electrophysiological events (Papi et al, 1995). Both the neural and neurochemical alterations by RF field may contribute towards the aberrant behavior including nociceptive behavior (Behari and Paul Raj, 2007).…”
Section: Introductionmentioning
confidence: 94%